Boundary Value Problems in Math Specialist Competence Development - Gulash, Koshanova; Venera, Mamaeva; Bayan, kuanbayeva; Amangul, Kokazhaeva; Bissenbayeva, Laura (International Journal of Psychosocial Rehabilitation, 2020)
Before we start off this section we need to make it very clear that we are only going to scratch the surface of the topic of boundary value problems. There is enough material in the topic of boundary value problems that we could devote a whole class to it. The intent of this section is to give a brief (and we mean very brief) look at the idea of boundary value problems and to give enough information to allow us to do some basic partial differential equations in the next research. Together with this, given manuscript demonstrates the necessity of professional education in educational system of the Republic of Kazakhstan for enhancement the professional preparation of the specialists